Revegetation of salt-affected land after mining: germination and establishment of halophytes. - Barrett, Gregory J. (Curtin University, 2000)
Gold and nickel mining are a common land use in the semiarid Eastern Goldfields region of Western Australia,, A frequent outcome of mining activity is highly saline landforms that result from the widespread use of hypersaline (> 50 g L(subscript)-1 NaCl) groundwater for mineral processing and hydraulic tailings reclamation, and from saline horizons in soils, subsoils and mullock. Under State government legislation, all mined land must be rehabilitated to a stable and sustainable landform at the completion of mining activities.There was little land rehabilitation carried out in the mining industry until the mid1980s. At that time, legislation was introduced and, in due course, guidelines were issued on recommended approaches to rehabilitation. Today, rehabilitation of disturbed areas is usually integrated into the mining program and has become the rule rather than the exception. There has, however, been limited innovation in recent years and the established methods are not suitable for every land rehabilitation scenario, especially those where very high salinity is an important factor. The aims of this thesis were to make a contribution towards a better understanding of the ecology of halophytes suitable for use in revegetation and the likely physical requirements for their sustainable establishment on post-mining landforms.In terms of germination, many of the halophytes currently used for rehabilitation of saline substrates are well suited in that they are able to germinate in solutions of up to 20 g L(subscript)-1 NaCl. Furthermore, when higher salinities are encountered, seed dormancy is induced until salinity is reduced to a level at which germination can occur. There were differences observed between germination of annual and perennial chenopods that reflected their successional roles where annual chenopods tend to have a higher salt tolerance and germinate more rapidly. I developed a tolerance index to enable different germination responses to be readily compared. Values for the tolerance index ranged from 5.7 to 25.3 for the halophytic species compared with a value of 0.2 for the glycophytic Secale cereale. Values for saltbushes (Atriplex) and bluebushes (Maireana) ranged from 6.5 to 9.8 while values for samphires (Halosarcia) were higher (10.7-17.4).Germination and early growth of taxa in the succulent genus, Halosarcia, were also studied. Though a member of the Chenopodiaceae, with a number of species occurring commonly throughout the region, Halosarcia spp. are not widely used in rehabilitation. This is in part attributable to the poor level of knowledge of germination and growth characteristics compared with saltbushes and bluebushes, many of which are widely used. Two species studied, H. halocnemoides subsp. halocnemoides and H. pruinosa, are more salt-tolerant for germination than some other chenopods more widely used. Furthermore, in terms of their early growth, each taxon continued to grow in salinities up to 40 g L(subscript)-1 NaCl, although root .Production and mass were reduced at that concentration. Another taxon, H. pergranulata subsp. pergranulata, was found to have a partial physical dormancy attributable to the testa, a phenomenon rare among halophytes. Dormancy was alleviated by scarification but was most effective where this occurred near the micropyle.Field trials were conducted to assess methods of rehabilitating severely salt-affected surfaces (EC(subscript)e > 50 dS m(subscript)-1). In the initial trial, a number of surface treatments, including ripping, rock mulching and mounding, were shown to reduce soil EC, in loam soils over a long period of time (seven years) compared with the control. In a subsequent trial, the use of good quality waste water, in conjunction with ponding banks, strongly promoted the establishment of vegetation by supplementing soil moisture and enhancing soil P although a reduction in soil EC(subscript)e was not observed. The depth and duration of ponding influenced the species that established and the cover achieved. Methods by which a soil cover could be established over hypersaline tailings surfaces were also investigated. The absence of a capillary break layer resulted in severe salinisation (EC(subscript)e > 100 dS m(subscript)-1) of a non-saline clay loam soil cover and likely severe difficulties in establishing and maintaining vegetation on the cover. Two types of capillary break layer, a synthetic membrane and a layer of coarse iron fayalite granules (nickel slag), were both effective at preventing the capillary rise of salts into the soil cover.The physical and biological characteristics of the shores of Lake Lefroy, a large salt lake in the Eastern Goldfields region, were analysed using multivariate techniques.Physical characteristics were strongly influenced by the orientation of the shore relation to the predominant winds, and by depth to the saline groundwater table. Plant species were distributed in zones across the lake shores with small changes in elevation resulting in substantial changes in species distributions. Those plant species occurring at the lowest elevations (Zone I), including Halosarcia spp., exhibited a very high tolerance of saline soil and groundwater through an ability to accumulate Na+ and Cl- and make the necessary osmotic adjustments, and a capacity to tolerance high groundwater levels. Under certain conditions, the lake shore environment could be a useful model for a rehabilitated landform.